Multi-omics analysis of the development and fracture resistance for maize internode - Wang, Xiaqing (Sci Rep, 2019)
The maize stalk is an important mechanical supporting tissue. The stalk fracture resistance is closely related to lodging resistance, and thus the yield. In this study, we showed that the basal zone (BZ) was more fragile than the middle zone (MZ) of the stalk internode before tasseling. In order to clarify the relationship between the different zones and fragile resistance between the internodes, we systematically analyzed the phenotypic, metabolomic and transcriptomic differences. The results indicated that the BZ zone had lower stalk strength, which corresponded to the results of less lignin, cellulose and hemicellulose than that of the MZ. The 27 highly enriched metabolites and 4430 highly expressed genes in the BZ mainly participated in pentose phosphate, and in ribosome and sterol synthesis pathways, respectively. In addition, the BZ had higher vascular bundles density but smaller size compared with the MZ. By contrast, the 28 highly enriched known metabolites and 4438 highly expressed genes in the MZ were mainly involved in lignin synthesis, and secondary metabolites synthesis, respectively, especially the phenylpropanoid synthesis. The results provide a deeper understanding of the relationship between development and fracture differences in stalk, and may facilitate the improvement of field management practice to reduce lodging.